Effectiveness of Problem-Based Learning Textbooks: ICARE's Pedagogical Approach to the Teaching Profession - Simbolon, Naeklan; Farihah, Farihah; Tanjung, Samsidar; Mursid, R (RIRAI Publisher, 2024)
The objectives of the study are to design a problem-based learning-based teaching profession textbook using the ICARE (Introduction, Connection, Application, Reflection, Extension) pedagogical approach; to assess the viability and efficacy of a PBL-based teaching profession textbook. Using the Borg and Gall paradigm, this research methodology called research and development (R&D). The study was carried out at the FIP Unimed, PGSD Department, Teaching Profession course. Students and instructors with expert validation—that is, specialists in learning design, visual design, and materials—were the study's subjects. Additionally, by carrying out field, small-group, and individual trials. Expert validation from subject matter experts, learning design experts, and graphic design experts is required for the entire product's results. In order to identify a teaching profession textbook based on PBL and assess its viability and efficacy, the following step involves conducting individual, small group, and field trials as well as carrying out revisions and analysis. ANOVA and/or the t-test will be used to examine the quasi-experimental approach (pretest-posttest with control group design) and the study's findings. The study's findings show that the PBL-Based Teaching Profession Textbook is deemed useful and appropriate for use in the classroom, with the potential to enhance student learning outcomes.